(untitled) (Revista científica Olimpia, 2025)
This article addresses the challenges and opportunities of professional advancement for early childhood educators as a decisive factor in the inclusive processes that must be developed in today’s society. The objective lies in implementing a strategy for the professional development of early childhood teachers aimed at achieving socio-educational inclusion for children with autism spectrum disorders. Some of the methods and techniques employed included structural-functional systemic modeling, documentary analysis, observation, statistical-mathematical methods, percentage analysis, frequency distribution tables, and the analysis of data collected through the application of empirical methods and techniques (descriptive statistics). The relevance of the proposal was verified through workshops focused on critical opinion and collective construction, and its effectiveness was validated via a pre-experiment conducted with early childhood educators in Azua province, Dominican Republic. Utilizing a mixed-methods approach that combines surveys and interviews with educators, the study examines perceptions and experiences related to their training and their ability to tackle challenges in the classroom. The results demonstrate that specialized training in autism spectrum disorders and differentiated teaching strategies are essential for promoting the successful inclusion of these students. This emphasizes the concept that teacher advancement is crucial for constructing inclusive classrooms that cater to the needs of all children.